Reconstruction of Legal Arrangements for Governance and Supervision of the Danantara Investment Management Agency in Ensuring Transparency and Preventing the Risk of State Financial Losses - Dhieno Yudhistira; Zudan Arief Fakrulloh (CV. Green Publisher Indonesia, 2026)
This study aims to analyze and reconstruct the legal arrangements for governance and supervision of the Daya Anagata Nusantara Investment Management Agency (Danantara) to ensure transparency and prevent the risk of state financial losses. The background of this study is based on the emergence of Danantara as a strategic instrument for state investment management that has special characteristics as a quasi-public entity, but is not yet supported by comprehensive and integrated legal regulations. The main problems studied include the unclear legal status of Danantara, the weakness of the governance system based on the principles of good corporate governance, as well as the potential for overlapping authorities due to the inefficiency of the supervisory mechanism involving multiple institutions, including the Financial Services Authority (OJK), the Supreme Audit Agency (BPK), and the Corruption Eradication Commission (KPK). By analyzing pertinent laws and regulations, legal doctrine, and pertinent ideas, this study employs a normative juridical method with a statutory and conceptual approach. The research results indicate that the current legal system still contains normative weaknesses in the form of regulatory disharmony, legal gaps in accountability, and unclear boundaries between business risks and state losses, as stipulated in Article 1, number 22 of Law Number 1 of 2004 concerning State Treasury. Therefore, legal reconstruction is needed, including strengthening the principles of good governance, a clear separation of the functions of regulator and operator, the establishment of an independent, integrated supervisory system, and the affirmation of legal accountability mechanisms